1998
DOI: 10.1161/01.res.82.11.1160
|View full text |Cite
|
Sign up to set email alerts
|

β 1 Integrins Participate in the Hypertrophic Response of Rat Ventricular Myocytes

Abstract: Abstract-Multiple signaling pathways have been implicated in the hypertrophic response of ventricular myocytes, yet the importance of cell-matrix interactions has not been extensively examined. Integrins are cell-surface molecules that link the extracellular matrix to the cellular cytoskeleton. They can function as cell signaling molecules and transducers of mechanical information in noncardiac cells. Given these properties and their abundance in cardiac cells, we evaluated the hypothesis that ␤ 1 integrin fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
129
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(139 citation statements)
references
References 89 publications
10
129
0
Order By: Relevance
“…This is in general agreement with the levels of ANF expression induced by other hypertrophic stimuli. For example, MAPK/ERK kinase-1 overexpression and phenylephrine and endothelin-1 stimulation results in ANF positively stained myocytes that range from 20 to 75% of total cells (7,(43)(44)(45). SB203580 (10 M) pretreatment of IL-1␤-stimulated cells partially inhibited ANF positively stained cells to 14 Ϯ 2% (Fig.…”
Section: Il-1␤-stimulated Hypertrophic Morphology and Anf Expression mentioning
confidence: 90%
“…This is in general agreement with the levels of ANF expression induced by other hypertrophic stimuli. For example, MAPK/ERK kinase-1 overexpression and phenylephrine and endothelin-1 stimulation results in ANF positively stained myocytes that range from 20 to 75% of total cells (7,(43)(44)(45). SB203580 (10 M) pretreatment of IL-1␤-stimulated cells partially inhibited ANF positively stained cells to 14 Ϯ 2% (Fig.…”
Section: Il-1␤-stimulated Hypertrophic Morphology and Anf Expression mentioning
confidence: 90%
“…OP is a well-characterized ligand of ␤ 1 -integrin receptors, which are involved in the adrenergically mediated atrial natriuretic peptide (hypotrophic) response in cardiomyocytes. 16 Xie et al 12 observed a suppressed atrial natriuretic peptide response in OP Ϫ/Ϫ hearts, too. Taken together, these findings suggest that OP is important for physiologically "intact" integrin-dependent cell functions essential for the response to increased cardiac load and injury in cardiomyocytes and fibroblasts.…”
Section: Op and The Heartmentioning
confidence: 98%
“…Moreover, FN-induced hypertrophy depended on intact integrin signaling, as evidenced by inhibition with anti-b1-integrin antibody, [26][27][28] and potentiated hypertrophy induced by the alphaadrenergic agonist PE. 29 In this study, we examine the hypothesis that FN and PE stimulation regulate the expression and localization of ILK, PARVA and PINCH1 proteins in cardiac myocytes where they may play a role in promoting cellular survival and transducing extracellular signals leading to hypertrophy.…”
mentioning
confidence: 99%